Epistemological beliefs and self-directed learning readiness of hospitality students: the necessary precursor to academic performance / Rahmat Hashim ...[et al.] - Hashim, Rahmat; Zali, Ahmad Nizan (ACRULeT, Faculty of Education & UiTM Press, 2009)
Throughout the philosophical literature, studies on epistemological beliefs have been well documented. However, within the educational context, this philosophical construct is a recent phenomenon. The purpose of this study is to explore the relationship between the conception of knowledge (epistemological beliefs) as measured by Schommer’s Epistemological Questionnaire (SEQ), learner perception of self-directedness as measured by Guglielmino’s Self-Directed Learning Readiness Scale (SDLRS) and academic achievement. The value of CMIN/DF was 2.22, below the recommended value of 3.0 (Kline, 1998). In this case, the U^sup 2^/df of 2.22 and CFI of .926 indicate an adequate fit between the hypothetical model and the sample data. The RMSEA for the measurement model was .077 (adequate fit). Other fit indices also point to an acceptable model fit between the model and the data (GFI = .921, AGFI = .879, CFI =.926). The entire model had an R2 of .064 and was not significant F(12, 210)=1.112, p > .05. The mediating effect of self-directed learning on GPA, falls short of statistical significance, b = .133, p = .074. However, when reviewing the effects of each of the regression coefficients, only 5 predictor variables (innate, simple, self assessment, goal setter, self control) were found to be of practical significance. MANOVA shows that there was no significant difference in epistemological beliefs, self regulated learning and gender at .05 level across GPA (Wilk’s lambda = .94, F = 1.153’ df = 5, p > .05).